2021
DOI: 10.1371/journal.pone.0249681
|View full text |Cite
|
Sign up to set email alerts
|

Assessing knowledge and attitudes toward epilepsy among schoolteachers and students: Implications for inclusion and safety in the educational system

Abstract: Several studies have evidenced inadequate knowledge about epilepsy and inappropriate seizure management, influencing quality of life and social inclusion of patients with epilepsy. Aim of the study was to estimate the knowledge and the attitudes toward epilepsy in schoolteachers and students in Italy. Custom-designed and validated questionnaires in Italian on general and specific knowledge, and social impact of epilepsy have been administered in a random sample of schoolteachers and students. Overall, 667 scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…13,14 Studies showed evidence of misconceptions, myths, and beliefs among different educated populations starting from school teachers as well as university students. [15][16][17] One study from Burkina Faso reported witchcraft as a cause of epilepsy. 18 However, there have been few available reports on misconception intervention and stigma reduction studies, especially in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Studies showed evidence of misconceptions, myths, and beliefs among different educated populations starting from school teachers as well as university students. [15][16][17] One study from Burkina Faso reported witchcraft as a cause of epilepsy. 18 However, there have been few available reports on misconception intervention and stigma reduction studies, especially in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Misconceptions, cultural beliefs, and stigmatization of epilepsy have been reported in different parts of the world; from western countries, Asian countries, and elsewhere 13,14 . Studies showed evidence of misconceptions, myths, and beliefs among different educated populations starting from school teachers as well as university students 15–17 . One study from Burkina Faso reported witchcraft as a cause of epilepsy 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, teachers in Riyadh and Khamis Mushait were found to have a high understanding of epilepsy [ 15 , 16 ]. Internationally, teachers' degree of epilepsy knowledge was poor in Kuwait, China, and Italy [ 17 - 19 ]. Although the level of knowledge is insufficient, the understanding and awareness of the etiology of epilepsy have experienced a significant change throughout time.…”
Section: Discussionmentioning
confidence: 99%
“…Produce development humans who can build themselves, and jointly responsible for the development of the nation. Functions of Non-formal Education, namely: 1) Non-formal education functions as a substitute (Hidayat et al, 2021), meaning that if the community member does not have a network with the Formal Education unit or has dropped out of school (DO) from Formal Education (Redondo et al, 2021), then he or she can attend Education through the Non-formal Education route (Marín & Espinoza, 2021); 2) Non-formal education functions as an addition to formal education, meaning that if the knowledge (Decembrotto, 2021), skills, and attitudes obtained by students in the formal education unit are deemed inadequate (Iannone et al, 2021), they can add them through non-formal education (Morgan et al, 2021); 3) Non-formal education functions as a complement (Fantozzi, 2021), meaning that if students in the formal education unit feel they still want to increase their knowledge and skills (Shantini et al, 2021a), then they can continue their education through the non-formal education pathway (Gultom, 2021). Such as: Computer Courses, Sewing Courses, Foreign Language Courses, and Personality Courses (Sokorutova et al, 2021).…”
Section: Introductionmentioning
confidence: 99%